Cover Picture: Catalytic Conversion of Alcohols into Carboxylic Acid Salts in Water: Scope, Recycling, and Mechanistic Insights (ChemSusChem 12/2016). Issue 12 (14th June 2016) - Zhang, Lei; Nguyen, Duc Hanh; Raffa, Guillaume; Trivelli, Xavier; Capet, Frédéric; Desset, Simon; Paul, Sébastien; Dumeignil, Franck; Gauvin, Régis M.
Abstract : The Cover picture shows how ruthenium pincer complexes catalyze the oxidation of alcohols into carboxylic acids in water, which acts as the oxygen source while H2 is released as the only by‐product, as illustrated by the bubbles. More details can be found in the Full Paper by Zhang et al. onpage 1413 in Issue 12, 2016 (DOI:10.1002/cssc.201600243 ).